Station-keeping of a high-altitude balloon with electric propulsion and wireless power transmission: A concept study. (November 2016) - van Wynsberghe, Erinn; Turak, Ayse
Abstract: A stable, ultra long-duration high-altitude balloon (HAB) platform which can maintain stationary position would represent a new paradigm for telecommunications and high-altitude observation and transmission services, with greatly reduced cost and complexity compared to existing technologies including satellites, telecom towers, and unmanned aerial vehicles (UAVs). This contribution proposes a lightweight superpressure balloon platform for deployment to an altitude of 25 km. Electrohydrodynamic (EHD) thrusters are presented to maintain position by overcoming stratospheric winds. Critical to maintaining position is a continual supply of electrical power to operate the on-board propulsion system. One viable solution is to deliver power wirelessly to a high-altitude craft from a ground-based transmitter. Microwave energy, not heavily attenuated by the atmosphere, can be provided remotely from a ground-based generator (magnetron, klystron, etc.) and steered electrically with an antenna array (phased array) at a designated frequency (such as 2.45 or 5.8 GHz). A rectifying antenna ("rectenna") on the bottom of the balloon converts waves into direct current for on-board use. Preliminary mission architecture, energy requirements, and safety concerns for a proposed system are presented along with recommended future work. Abstract : Highlights: A geostationary high-altitude balloon platform is described. Feasible, based on existing, proven technologies. Superpressure balloon, electrohydrodynamic thrusters, wireless power transmission. Potential applications and benefits are discussed. Mission architecture, energy needs, safety concerns, and future work discussed.